The Prevalence and Estimate of Treatment Need for First Permanent Molar of 6-12 Years Old Children - Jamilah, Wardati; Agustin, Afifah; Salsabila, Selvi; Herawati, Nova; Yuzar, Yessi (POLTEKKES KEMENKES PADANG, 2024)
The M1 tooth is the first tooth to erupt at the age of 6-7 years which becomes a guide for the growth of other permanent teeth. Early eruption, tooth anatomy, poor child behavior and lack of parental knowledge make M1 teeth most at risk of caries. The prevalence of M1 dental caries in children aged 6-12 years is the number of people who experience caries in one population. This study to determine the prevalence and estimated need for M1 care for children aged 6-12 years at AlFalah Islamic Elementary School, Bukittinggi City. This study use cross sectional research design . The number of samples was 431 (total population). Data collection was through direct observation (examination) using the DMFT index and guided interviews with a questionnaire. Data analysis used the chisquare test , α: (0.05) and the mean-Whitney test. The prevalence of M1 caries in children aged 6-12 years was 45% with a mean DMFT of 0.85. Mark The p value for gender, age group and brushing frequency is 0.04 < 0.05, meaning that there are differences in the prevalence of M1 caries based on gender, age group and frequency of brushing teeth regarding M1 dental caries. To estimate the need for restoration treatment for M1 teeth, the p value for gender is 0.02 < 0.05, meaning there is a difference in the need for M1 caries restoration for women and men, the p value for age group is 0.3 > 0.05, meaning there is no difference in need for restoration. M1 dental caries in children aged 6-9 and 10-12. The high prevalence of M1 caries occurs due to several interconnected factors. The prevalence of M1 caries in children aged 6-12 years reaches 45% with the average child having experience of 1 M1 tooth caries and the need for 1 M1 tooth filling. This must be a concern as a form of contribution to realizing a caries-free Indonesia by 2030.